Double-label immunohistochemistry to assess labyrinth structure of the mouse placenta with stereology. (May 2020) - De Clercq, Katrien; Lopez-Tello, Jorge; Vriens, Joris; Sferruzzi-Perri, Amanda N.
Abstract: In mice, the labyrinth zone of the placenta exchanges nutrients and gases between mother and fetus. This placental zone is complex in structure and defects in its morphogenesis can compromise substrate exchange and thus, fetal growth and viability. Numerous mouse models involving genetic and environmental manipulation show abnormalities in labyrinth zone size. However, further structural analysis, normally undertaken using ultrathin resin sections, can pose practical constraints. Here, we validate the use of stereology on paraffin-embedded sections double-labelled for lectin and cytokeratin as a cheap, fast and robust alternative for analysing the structure of the mouse placental labyrinth. Highlights: Alternative method to facilitate labyrinth morphometric analysis. Protocol uses antibodies that bind lectin and cytokeratin in one placental section. Protocol allows fetal endothelial cells and trophoblast to be identified. These sections can be used for the stereological analysis of labyrinth structure. Labyrinth constituents, barrier thickness and surface area can all be measured.